A survey of the fishery resource of Perch Lake, Monroe County, Wisconsin - Babros, Timothy E. (My University, 1985)
An inventory of the fishery resource of Perch Lake, Monroe County, Wisconsin was conducted to determine the species present, species population structure, community structure and lake morphometry. Two laps of the shoreline were electrofished on four nights during a three week period in September 1983 and seine hauls were conducted prior to electrofishing to assess young-of-the-year and forage species abundance. Analyses of the species population structure and condition showed that largemouth bass (Micropterus salmoides) and northern pike (Esox lucius) populations are growing favorably but these species are represented by young populations and very few large predators were observed. Assessment of the most abundant panfish species sampled revealed normal population structure for bluegill (Lepomis macrochirus) and pumpkinseed sunfish (h. gibbosus) and showed that these fishes were in average to good condition. In addition the growth rates of bluegill and pumpkinseeds were also found to be normal. The electrofishing sample mostly contained young-of-the-year black crappies (Pomoxis nigromaculatus) and an accurate assessment of population structure, growth rate and condition of that species was impossible. Two rough fish species that were observed in high abundance were white sucker (Catostomus commersoni) and common carp (Cyprinus carpio) and the sample contained many older individuals of both species. Assessments of the growth rates and condition indicated that common carp were approaching levels of overabundance; the high estimated number of white suckers suggested that this species may have been approaching overabundance as well. Biomass measurements and an analysis of the community structure indicated a dominance of rough fish species in Perch Lake and it was concluded that their removal would enhance the overall community structure. Structural indices also showed that predator populations were young and were providing suboptimal quality sport fishing. Results of the morphometric survey revealed that Perch Lake is characterized by a very uniform depth, narrow littoral zone, and minimal habitat for fish species. Predator populations are young and a direct result of stocking efforts. Although panfish populations are self-sustaining and presently provide quality fishing, rough fish removal would likely enhance community structure for sport fishing. Continued stocking of largemouth bass and northern pike will be necessary in the future unless adequate spawning habitat can be provided since the natural reproduction of these species is minimal. The recent installation of fish cribs in the lake will benefit all species present and the strong public interest observed in the locality suggests favorable cost/benefit ratios for management programs.
Keywords: Fishes -- Wisconsin -- Perch Lake (Sparta); Perch Lake (Sparta, Wis.)